2015
DOI: 10.1002/ejoc.201403511
|View full text |Cite
|
Sign up to set email alerts
|

Iron‐Catalyzed Tandem Cyclization and Cross‐Coupling Reactions of Iodoalkanes and Aryl Grignard Reagents

Abstract: Iron-Catalyzed Tandem Cyclization and Cross-Coupling Reactions of Iodoalkanes and Aryl Grignard Reagents. -The reaction is assumed to proceed via a radical process. In the case of substituted alkenes (XV) and (XVII) an internal cyclization precedes the cross-coupling pathway, presumably due to the steric congestion. -(KIM, J. G.; SON, Y. H.; SEO, J. W.; KANG*, E. J.; Eur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 72 publications
2
12
0
Order By: Relevance
“…In 2018, the Diao group showed that a wide range of alkylbromide containing alkenes underwent intramolecular dicarbofunctionalization with a variety of (hetero)aryl and alkyl bromides (Scheme 50). [ 113 ] In contrast to the previous reports [ 114‐118 ] that the dicarbofunctionalization of alkenes was restricted to the formation of five‐membered rings, this method could afford piperidine derivatives by 6‐exo‐trig cyclization. Thorpe‐Ingold effect [ 119 ] played a crucial role on the efficiency of the radical cyclization, as the unsubstituted carbochain favored direct coupling with another electronphile, such as arylbromide, prior to cyclization.…”
Section: Intramolecular Dicarbofunctionalization Of Alkenes Via Cyclimentioning
confidence: 95%
“…In 2018, the Diao group showed that a wide range of alkylbromide containing alkenes underwent intramolecular dicarbofunctionalization with a variety of (hetero)aryl and alkyl bromides (Scheme 50). [ 113 ] In contrast to the previous reports [ 114‐118 ] that the dicarbofunctionalization of alkenes was restricted to the formation of five‐membered rings, this method could afford piperidine derivatives by 6‐exo‐trig cyclization. Thorpe‐Ingold effect [ 119 ] played a crucial role on the efficiency of the radical cyclization, as the unsubstituted carbochain favored direct coupling with another electronphile, such as arylbromide, prior to cyclization.…”
Section: Intramolecular Dicarbofunctionalization Of Alkenes Via Cyclimentioning
confidence: 95%
“…Another recurring motif in recent work is the direct combination of iron-catalyzed cross-coupling with other transformations to achieve cascade reactions. 23,24 A notable example of this approach is the dual use of an iron catalyst for the ring opening of a pyrone and its consecutive crosscoupling (Scheme 3). 25 Fürstner and co-workers applied this cascade reaction in the synthesis of a natural product analogue with anticancer activity.…”
Section: Short Review Syn Thesismentioning
confidence: 99%
“…The results of several radical clock and radical trap experiments are consistent with the generally accepted involvement of radicals in iron-catalyzed cross-coupling reactions of alkyl halides (also see section 3.2). 21,23,48,66,69,71 However, most of these experiments have been criticized for not being unambiguous in the case of organometallic systems. 5f Strong support for the suggested mechanism comes from the work of the Neidig group, who found the iron(II) complexes PhFeBr(SciOPP) and Ph 2 Fe(SciOPP) to react with bromocycloheptane at catalytically relevant rates.…”
Section: Scheme 14 Proposed Catalytic Fe(ii)-fe(iii) Cycle Of Iron-camentioning
confidence: 99%
“…Since then, several reports of alkyl halide cross-coupling reactions have been reported [ 53 ]. In 2015, Kang and co-workers described a FeCl 2 -catalyzed tandem cyclization/cross-coupling reaction of alkyl iodides 1 with aryl Grignard reagents 2 to give arylmethyl-substituted pyrrolidines and tetrahydrofurans 3 in poor to excellent yield ( Scheme 3 ) [ 54 ].…”
Section: Reviewmentioning
confidence: 99%